Kepemimpinan Transformatif di Ma’had Tahfidz Al-Husni: Studi Living Qur’an QS. An-Nisa Ayat 59 dan 83 - Ahmad Nurul Mushthofa; A. Fauzi Aziz; Salim Ashar (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
This study aims to analyze the transformational leadership of ulil amri from a living Qur’an perspective based on Surah An-Nisa verses 59 and 83 and its implications for the character development of hafidzoh at Ma’had Tahfidz Al-Husni. This research employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation. Data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that the values of obedience, responsibility, and wisdom embedded in Surah An-Nisa verses 59 and 83 are implemented through exemplary leadership, character development programs, and institutional policies oriented toward the internalization of Qur’anic values. This implementation fosters internal motivation among hafidzoh to practice honesty, discipline, responsibility, and justice in their daily lives. Furthermore, transformational leadership of ulil amri not only produces formal compliance but also develops sustainable collective awareness. Therefore, transformational leadership based on the living Qur’an approach is proven to be effective in systematically and sustainably shaping the character of hafidzoh within the context of Qur’an-based educational institutions.